El desarrollo de los FIBRA en el Perú - Gordillo Soto, Rocío (2023)
FIRBI or FIBRA are vehicles that have revolutionized traditional real estate investment. The objective of these vehicles is to give access to all types of investors, including natural persons, to the real-estate market through the acquisition of shares in these vehicles that invest in incomegenerating real estate assets, and that also enjoy of tax benefits.International experience demonstrates that understanding the particular market of each country and based on this, constantly improving the regulation of FIRBI or FIBRA is what generates the development of this market.